C-reactive protein as a tool for monitoring response to treatment in dogs with acute hemorrhagic diarrhea syndrome - Sänger, Florian; Unterer, Stefan; Werner, Melanie; Dörfelt, René (Frontiers in Veterinary Science, 2023)
Objectives: C-reactive protein (CRP) is an established marker for systemic inflammation in dogs that is especially elevated in dogs with sepsis. Some dogs with acute hemorrhagic diarrhea syndrome (AHDS) develop bacterial translocation and consequent sepsis during hospitalization. This study aimed to evaluate the course of CRP plasma concentrations during hospitalization and its correlation with clinical and other laboratory variables in dogs with AHDS. Methods: In this prospective, observational study, CRP was evaluated on days 0, 1, 2 and 3 in 27 client-owned dogs who presented with AHDS. Clinical examination data, blood pressure, acute patient physiologic and laboratory evaluation (APPLE) full and APPLE fast scores, and canine hemorrhagic diarrhea severity (CHDS) index were measured on the same days to evaluate the severity of the disease. Results: Twenty-five of the 27 dogs were discharged from hospital. Nineteen dogs received antimicrobial treatment due to sepsis or neutropenia. CRP values were mildly elevated on day 0 (median 27.3 mg/L; 1.0–125.8 mg/L) and markedly elevated on day 1 (median 88.9 mg/L; 1.4–192.7 mg/L). CRP concentrations decreased gradually over the following days. Moreover, CRP concentrations correlated moderately with albumin, leucocyte count, neutrophil count, and APPLE full and fast scores, but not with antimicrobial treatment. Conclusion and relevance: CRP concentrations were significantly elevated in patients with AHDS. In this study population, CRP did not help in detecting the requirement of antimicrobial treatment in dogs with AHDS. Nevertheless, as CRP can monitor the response to treatment, regular analysis can guide treatment.